2021
DOI: 10.1038/s41598-021-00965-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diffraction peak, network topology, and amorphous-forming ability in silicon and silica

Abstract: The network topology in disordered materials is an important structural descriptor for understanding the nature of disorder that is usually hidden in pairwise correlations. Here, we compare the covalent network topology of liquid and solidified silicon (Si) with that of silica (SiO2) on the basis of the analyses of the ring size and cavity distributions and tetrahedral order. We discover that the ring size distributions in amorphous (a)-Si are narrower and the cavity volume ratio is smaller than those in a-SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…While we interpreted the TDA results based on the ring statistics computed using the so-called King’s definition (Figure ), we also investigated other definitions. Three definitions (King, Guttman, and primitive (most common) ) have been adopted for silica glasses. ,,,, We found that the ring statistics computed according to Guttman’s definition do not show any swap at the temperatures obtained using TDA, unlike the ring statistics computed using King’s and the primitive definitions. Figure shows the comparison of the −Si–O– ring statistics computed using the three different definitions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…While we interpreted the TDA results based on the ring statistics computed using the so-called King’s definition (Figure ), we also investigated other definitions. Three definitions (King, Guttman, and primitive (most common) ) have been adopted for silica glasses. ,,,, We found that the ring statistics computed according to Guttman’s definition do not show any swap at the temperatures obtained using TDA, unlike the ring statistics computed using King’s and the primitive definitions. Figure shows the comparison of the −Si–O– ring statistics computed using the three different definitions.…”
Section: Discussionmentioning
confidence: 86%
“…Our TDA results reveal that the topology of the partial −Si− Si− network changes at the density maximum and minimum 27,51,[77][78][79][80][81][82][83]84 The reasons for this are probably the following: Silica glass is typically categorized as a "tetrahedral liquid" or "water-type liquid," which includes water, silicon, germanium, and beryllium fluoride. 2,85 Among these, water has been studied the most intensively because of its ubiquity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, Kohara et al have compared the network topology of liquid and solidified (crystalline and amorphous) Si with those of SiO 2 and concluded that the tetrahedral corner-sharing network of AX 2 , in which A is a fourfold cation and X is a twofold anion, as indicated by the FSDP, is an important structural motif for the good amorphous-forming ability and can rule out Si as a good amorphous former. 48) To study the network topology of g-SiO 2 in detail, a novel topological analysis, persistent homology, 49) an emerging mathematical tool for characterizing the shapes of data, was introduced together with the conventional (Si O) n ring size distribution analysis. 50),51) Primitive rings are identified by searching the shortest closed path along with SiO bonds and cannot be decomposed into smaller rings.…”
Section: Understanding Diffraction Patterns and Uncovering Network To...mentioning
confidence: 99%
“…The Born-Oppenheimer molecular dynamics calculations were performed with the CP2K package [30] using the generalized gradi-ent approximation and the PBEsol exchange-correlation functional [31]. Basically, the employed FPMD technique was similar to that used in previously published reports on similar glass systems [32][33][34]. Randomly generated initial configurations of 940 atoms, (AgI) 0.1 (As 2 S 3 ) 0.9 , and 1050 atoms, (AgBr) 0.5 (As 2 S 3 ) 0.5 , were optimized using RMC++ code [35] to obtain a good agreement with neutron and high-energy X-ray diffraction results.…”
Section: First-principles Molecular Dynamics Modelingmentioning
confidence: 99%